Transition-Metal-Catalyzed Rapid Synthesis of Imidazo[2,1-b]thiazoles: Access to Aza-Fused Heterocycles via Aerobic Oxidative Coupling of 2-Aminothiazoles and Acetophenones - Basak, Soumya Jyoti; Paul, Pratap; Dash, Jyotirmayee (Synthesis, 2024)
We report an efficient synthesis of 6-substituted imidazo[2,1-b]thiazoles from 2-aminothiazoles and acetophenones through intramolecular cyclization of in situ generated thiazolium ylides. This one-pot cascade process efficiently forms two C–N bonds and is facilitated by both Cu(OTf)2/KI and FeCl3/ZnI2 systems. The method utilizes commercially available starting materials and features mild reaction conditions, tolerance to different functional groups, and ease of operation. The synthetic applicability has further been demonstrated through post-modification of imidazo[2,1-b]thiazole analogues.
Keywords: 2-aminothiazoles; acetophenones; 6-phenylimidazo[2,1-b]thiazoles; thiazolium ylide intermediate; transition-metal-catalyzed C–H bond activation